Cancer burden and alarm signals: a community based study from Kerala, India - Mathew, Geethu; Sebastian, Shaliet Rose; Benjamin, Anoop I.; Goyal, Vinay; Sushan, Abey; Joseph, Jiju; L., Sheeja A. (International Journal of Research in Medical Sciences, 2020)
Background: Cancer is emerging as a major public health concern in many countries including India. Kerala state has the highest burden of cancer in the country. Objective of this study was to estimate the prevalence of diagnosed cancers, warning signs and selected risk factors of cancer in Kadapra Panchayath of Pathanamthitta district, Kerala. Methods: A total of 16,391 population was covered by door to door survey using a structured questionnaire. The questionnaire collected information on the sociodemographic variables of the residents, source of water supply, warning signs of cancer and details of diagnosed cancer cases. Results: The mean age of the population was 40.9+21 years. The prevalence of diagnosed cases of cancer in our study population was 776/100,000 population. Breast cancer was the most common cancer (43.5%) identified in the population. The prevalence of any warning sign among the study population was 220/100,000 population. Breast lump was the common warning sign identified. Increasing age and female gender were the factors found to be significantly associated with cancer. Conclusions: As prevalence of cancer was found to be high in this population, an active community based screening along with teaching self-breast examination to the women in the community are required. Improving community awareness could help in early diagnosis, treatment and prevention. Soil and water testing for carcinogens is recommended.